2021
DOI: 10.1155/2021/6637180
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphataemic Rickets Secondary to Raine Syndrome: A Review of the Literature and Case Reports of Three Paediatric Patients’ Dental Management

Abstract: Raine Syndrome (RS) also referred to as lethal osteosclerotic bone dysplasia describes an exceptionally rare autosomal recessive disorder with an estimated prevalence of <1 in 1,000,000. Endocrinological manifestations such as hypophosphataemic rickets depict a recent finding within the phenotypic spectrum of nonlethal RS. The dental sequelae of hypophosphataemic rickets are significant. Spontaneous recurrent abscesses on noncarious teeth result in significant odontogenic pain and multiple dental interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The prevalence of RS is one in a million individuals with Arab ancestry, accounting for most cases. 7,8 According to previous cases, RS is fatal within the first few weeks of life because of pulmonary hypoplasia and choanal atresia/stenosis. However, several cases have been found in which the patient survived into adolescence or adulthood, implying a non-lethal type of RS, and highlighting that lethality is not essential for diagnosis.…”
Section: Discussion:-mentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of RS is one in a million individuals with Arab ancestry, accounting for most cases. 7,8 According to previous cases, RS is fatal within the first few weeks of life because of pulmonary hypoplasia and choanal atresia/stenosis. However, several cases have been found in which the patient survived into adolescence or adulthood, implying a non-lethal type of RS, and highlighting that lethality is not essential for diagnosis.…”
Section: Discussion:-mentioning
confidence: 99%
“…However, several cases have been found in which the patient survived into adolescence or adulthood, implying a non-lethal type of RS, and highlighting that lethality is not essential for diagnosis. 5,6,8 Moreover, there is no explicit distinction between the lethal and non-lethal forms of RS in terms of genetic and phenotypical expression. 12 The most common findings in newborns with RS are depressed nasal bridge, micrognathia, underdeveloped midface hypoplasia, wide fontanelles, microcephaly, tented upper lip, low-set ears, prominent exophthalmos, choanal atresia, hyperplastic gum, cleft soft palate.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…FAM20C variants cause Raine syndrome, along with hypophosphatemia ( 44 , 45 ), cerebral calcifications, osteosclerosis of long bones, facial and acral dysmorphism, and dental decay. FAM20C enhances DMP1 expression ( 46 ) and phosphorylates FGF23, causing impairment of GALNT3-mediated O-glycosylation and making FGF23 prone to cleavage ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought to be caused by ameloblasts that have been affected by local and systemic factors during the formation of enamel [1]. Studies have reported on eruption disorders in patients with developmental enamel defects other than MIH [2,3]. The eruption is a dynamic process that begins at the initial positioning of the tooth in the alveolar bone and continues until the final positioning at which it is occluded by a dental antagonist.…”
Section: Introductionmentioning
confidence: 99%